Pharmacokinetic interaction between single and multiple doses of darunavir, in combination with cobicistat or ritonavir, and single-dose dabigatran etexilate in healthy adults - Sandy Van Hemelryck; Erika Van Landuyt; Jay Ariyawansa; Martyn Palmer; Martine J. C. Kothe; Caroline Pollefliet (SpringerOpen, 2024)
Abstract Objective Darunavir (DRV) is a P-glycoprotein (P-gp) inhibitor. Dabigatran etexilate, prodrug of the anticoagulant dabigatran, is a P-gp probe substrate. This study evaluated the effect of single and multiple doses of DRV, coadministered with cobicistat (COBI) or ritonavir (rtv), on the pharmacokinetics (PK) of single-dose dabigatran etexilate. Methods This was an open-label, fixed-sequence, single-center, 2-panel, phase 1 study in which healthy adult participants were equally divided over 2 panels. In panel 1, participants received single and multiple doses of DRV/COBI 800/150 mg coadministered with single-dose dabigatran etexilate 150 mg. In panel 2, participants received single and multiple doses of DRV 800 mg + rtv 100 mg coadministered with single-dose dabigatran etexilate 150 mg. Key PK parameters evaluated were maximum plasma concentration (Cmax) and area under the plasma concentration-time curve from time zero to infinity (AUCinf) for free and total dabigatran. Results Overall, 28 participants were enrolled and treated (n = 14 per panel). Dabigatran Cmax and AUCinf increased 2.64-fold after a single dose of DRV/COBI and 1.99- and 1.88-fold, respectively, after multiple doses of DRV/COBI. Dabigatran Cmax and AUCinf increased 1.64- and 1.72-fold, respectively, after a single dose of DRV + rtv and 1.22- and 1.18-fold, respectively, after multiple doses of DRV + rtv. In both panels, the most commonly reported adverse events were diarrhea and headache. Conclusion Findings of increased dabigatran exposure with DRV/COBI or DRV + rtv coadministration indicate an inhibitory effect of single-dose boosted DRV on P-gp, and a mixed inhibitory/inductive effect of multiple doses of boosted DRV on P-gp. Trial registration ClinicalTrials.gov, NCT04208061 . Registered December 19, 2019